Mandarin Chinese 是……的 shì…de construction as an example of a cleft structure - Wielosz, Sebastian (Papers in Linguistics, 2021)
Cleft sentences appear in a lot of languages, no matter which language group or family they represent, yet they might have different syntactic and semantic properties due to the typological variety of world’s languages. The majority of articles and monographs on this topic have been written to recount a certain grammatical relation in English, as this is the language in which the term cleft sentence was coined. Linguists noticed years ago that similar structures exist in other languages. Among them there is Mandarin Chinese, which has a structure that meets all the requirements for a frame structure. Yet linguists do not often see the resemblance between the是……的 shì...de construction and analogical sentence structures in other languages and do not attribute the name cleft sentence to it. The main purpose of this paper is to elaborately present what cleft structures are, as well as to prove that the 是……的shì...de structure is in fact this type of sentence. The first part is supposed to provide general information concerning cleft structures in a natural language. The second part is a presentation of most important issues related to the cleft structure in Mandarin Chinese.